2018
DOI: 10.1139/cjp-2017-0678
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and conductivity of PVdF-co-HFP/LiClO4polymer electrolytes

Abstract: In this study, it was aimed to prepare a series of PVdF-co-HFP based electrolytes with different LiClO4 loadings and to investigate their chemical and electrical properties in detail. For this purpose, PVdF-co-HFP based electrolytes with different LiClO4 loadings (1–20 weight %) were prepared using solution casting method. X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric (TGA) –differential thermal and dielectric spectroscopy analysis of PVdF-co-HFP/LiClO4 were performed to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This is attributed to the fact that the porosity and β ‐phase fraction of this composite film reached their maximum, as confirmed in Figure 3 and Table 3, resulting in a significantly higher relative dielectric constant in the composite film. It is also shown that the dielectric loss is only 0.49 at frequency of 10 Hz, which is much smaller than most of the data reported in literature at the same level of dielectric constant 45,75 . Therefore, the enhancement of net dipole moment is beneficial to the improvement of polarization and dielectric constant of P(VDF‐HFP)/CaCl 2 ·6H 2 O composite films.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…This is attributed to the fact that the porosity and β ‐phase fraction of this composite film reached their maximum, as confirmed in Figure 3 and Table 3, resulting in a significantly higher relative dielectric constant in the composite film. It is also shown that the dielectric loss is only 0.49 at frequency of 10 Hz, which is much smaller than most of the data reported in literature at the same level of dielectric constant 45,75 . Therefore, the enhancement of net dipole moment is beneficial to the improvement of polarization and dielectric constant of P(VDF‐HFP)/CaCl 2 ·6H 2 O composite films.…”
Section: Resultsmentioning
confidence: 67%
“…The capacitance (C) of each sample was determined as a function of frequency ranging from 1 Hz to 100 kHz at room temperature. The dielectric constant ()εr$$ \left({\varepsilon}_r^{\prime}\right) $$ or real part of the relative permittivity, dielectric loss tangent (tan δ ), and ionic conductivity ( σ ) of all samples could be derived from the following relationships 45–47 : εrgoodbreak=C0.1emtε0A,tanδgoodbreak=εrεr,σgoodbreak=tRbA,$$ {\varepsilon}_r^{\prime }=\frac{C\kern0.1em t}{\varepsilon_0A},\tan \delta =\frac{{\varepsilon^{\prime}}_r^{\prime }}{\varepsilon_r^{\prime }},\sigma =\frac{t}{R_bA}, $$ where ε 0 represents the vacuum permittivity (8.854 × 10 −12 Fm −1 ), and t and A denote the film thickness (m) and the area of the electrode contact (m 2 ), respectively. εr$$ {\varepsilon^{\prime}}_r^{\prime } $$ represents the imaginary component of the relative permittivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations